2021
DOI: 10.3390/jcm10143164
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressor-Sparing Strategies in Patients with Shock: A Scoping-Review and an Evidence-Based Strategy Proposition

Abstract: Despite the abundant literature on vasopressor therapy, few studies have focused on vasopressor-sparing strategies in patients with shock. We performed a scoping-review of the published studies evaluating vasopressor-sparing strategies by analyzing the results from randomized controlled trials conducted in patients with shock, with a focus on vasopressor doses and/or duration reduction. We analyzed 143 studies, mainly performed in septic shock. Our analysis demonstrated that several pharmacological and non-pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 148 publications
(171 reference statements)
0
25
0
Order By: Relevance
“…The fact that most uncoupled patients showed an increase in VO 2 after therapeutic interventions could be a further argument for targeting V-A coupling during resuscitation, as marker of tissular perfusion. This therapeutic option might help in better choosing the responsive patients, as a vasopressor-sparing strategy ( 32 ). The norepinephrine infusion alters V-A coupling with an increase in Ea >> Ev ( 30 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that most uncoupled patients showed an increase in VO 2 after therapeutic interventions could be a further argument for targeting V-A coupling during resuscitation, as marker of tissular perfusion. This therapeutic option might help in better choosing the responsive patients, as a vasopressor-sparing strategy ( 32 ). The norepinephrine infusion alters V-A coupling with an increase in Ea >> Ev ( 30 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The norepinephrine infusion alters V-A coupling with an increase in Ea >> Ev ( 30 , 33 ). Targeting primarily the MAP of 65 mmHg might sustain an unnecessary ( 34 ) and possibly an unfavorable prolonged energetic state because of increased cardiac afterload ( 32 ). Algorithms using the monitoring dynamic arterial elastance were proposed in ICU and they demonstrated that early weaning of norepinephrine may be associated with better tissue perfusion ( 12 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vasopressor weaning is a dynamic process that requires a careful evaluation of the different components of the cardiovascular system ( 3 ). Physicians should consider the clinical benefit of fluid expansion in arterial hypotension during norepinephrine weaning.…”
Section: Discussionmentioning
confidence: 99%
“…Fluid therapy and norepinephrine are the main hemodynamic treatments for septic shock ( 1 , 2 ). Once the patient starts recovering, vascular tone progressively improves, and the hemodynamic de-escalation phase begins ( 1 , 3 ). Norepinephrine weaning is an important part of the therapeutic process when treating patients with septic shock ( 2 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interesting most of the literature has focused on fluid during shock resuscitation but maintenance fluid therapy and creep fluid may account for 30% of fluid balance ( 28 ). Oral water may not replace iv fluid but it's long-acting cardiovascular effects may be of interest during optimization and weaning process of shock patients supported by vasopressor and fluid ( 29 ). In addition, using oral tap water may be of interest in term of fluid balance because plasma volume effect and body elimination can be modulated by adding glucose or combining different type of water (tap, saline, sugar).…”
Section: Discussionmentioning
confidence: 99%